Efeito tripanocida da (E)-1-(4-aminofenil)-3-(4-nitrofenil)prop-2-en-1-ona e ação sobre enzimas de tripanossomatídeos - Silva, Brenna Pinheiro (2023)
Chagas disease is included in the group of neglected tropical diseases, as a parasitic infection caused by the protozoan Trypanosoma cruzi, affecting approximately 6 to 8 million people in Latin America and 2.4 million people in Brazil. Benznidazole (BZN), the drug of choice, has limited efficacy and serious adverse effects, making the search for new therapeutic tools urgent. The study and identification of vital biochemical targets for T. cruzi is an important strategy for the development of selective inhibitors capable of interfering with these metabolic pathways and causing the death of the parasite. In this context, chalcones are an important class of natural compounds that have a wide spectrum of biological activities and whose simplified structure allows the synthesis of analogues, which have shown advantageous properties for the development of antichagasic drugs. Therefore, the aim of the present study was to evaluate the trypanocidal effect of (E)-1-(4-aminophenyl)-3-(4-nitrophenyl)prop-2-en- 1-one (CPA4NO2) and its action on enzymes of trypanosomatids – cruzain and trypanothione reductase. Thus, the cytotoxicity was evaluated on the LLC-MK2 host cells, through the MTT reduction method, and the trypanocidal effect was evaluated on the epimastigotes forms (cultured in LIT medium, at 28oC, in a BOD oven) and trypomastigotes (obtained through the infection of cells LLC-MK2 and cultivated in DMEM medium, at 37oC and 5% of CO2) of strain Y of T. cruzi, being then determined the Index of Selectivity (SI). In addition, computational analysis of the interactions involving the substances under study and the enzymes cruzain and trypanothione reductase was carried out, through molecular docking assays. All tests were performed in triplicate and the mean results of three independent experiments were used for statistical analysis (one-way ANOVA test, with Bonferroni post- test) with p<0.05. CPA4NO2 did not show cytotoxicity at the concentrations used (1000 – 15.6 μM), and in the investigation of the antiparasitic effect, it was able to inhibit the growth of epimastigotes in the three times tested (IC50 24h: 171.4 ± 13.6 μM; IC50 48h: 99.44 ± 4.46 μM; IC50 72h: 27.91 ± 1.48 μM) and reduce the viability of trypomastigotes in almost all tested concentrations, exhibiting an LC50 value (161.4 ± 33.9 μM) three times lower than that presented by the reference drug. Therefore, when compared to BZN, it showed an IS > 6.19. Through the use of computational tools, it was possible to infer that the synthetic chalcone CPA4NO2 showed a good interaction with the enzymes cruzain and trypanothione reductase, however, in possibly allosteric sites. Finally, this work highlights the biotechnological potential of the chalcone CPA4NO2, making it a promising candidate for the development of new antichagasic therapies.